An automated production targeting goal programming framework for oil sands mine planning considering organic rich solids. Issue 2 (2nd April 2020) - Maremi, Ahlam; Ben-Awuah, Eugene; Pourrahimian, Yashar
ABSTRACT: In oil sands mining, bitumen and fines contents are used to predict ore processability. However, experimental results show that certain solid fractions known as Organic Rich Solids (ORS) negatively affect the overall bitumen recovery. A conceptual mine planning framework based on a goal programming model for oil sands production scheduling and waste management is presented. Bitumen recovery is additionally adjusted based on the ORS content. The model features automated production targeting (APT) and limited duration stockpiling constraints that optimize the annual production capacities. The model is implemented with two scenarios. Scenario 1 uses processing recovery calculated based on Alberta Energy Regulatory requirements while Scenario 2 uses processing recovery additionally adjusted based on ORS content. Results for Scenario 1 show a 3.46% overestimation of net present value compared to Scenario 2. The APT constraints provide planners a robust and efficient technique for determining annual production tonnages with minimum periodic variations.